Distinct Characteristics of COVID-19 Infection in Children - Han, Xuejiao; Li, Xuemei; Xiao, Yinan; Yang, Ruoning; Wang, Yang; Wei, Xiawei (Frontiers in Pediatrics, 2021)
SARS-CoV-2, a member of the family coronaviridae, has triggered a lethal pandemic termed coronavirus disease 2019 (COVID-19). Pediatric patients, mainly from families with a cluster of infection or a history of exposure to epidemic areas, get infected via direct contacts or air-borne droplets. Children (aged below 18 years) are susceptible to COVID-19, with an average incubation period of about 6.5 days. Most cases present asymptomatic or common cold symptoms such as fever, cough, and myalgia or fatigue, which is milder than adult patients. Besides, most abnormal laboratory and radiologic findings in children with COVID-19 are non-specific. Since no specific chemotherapeutic agents have been approved for children, timely preventive methods could effectively forestall the transmission of SARS-CoV-2. To date, mostly studied cases have been adults with COVID-19, whereas data on pediatrics patients remain poorly defined. We herein conducted a literature review for papers published in PubMed and medRxiv (preprints) between December 2019 and December 2020 that reported on pediatrics patients (aged below 18 years) with a confirmed COVID-19 diagnosis. In this review, we summarized and discussed the pathogenesis, epidemiology, and clinical management of COVID-19 in pediatrics patients to improve our understanding of this new disease in children.